Investitionsneutrale Besteuerung des ökonomischen Gewinns: ein Abriss jüngerer Forschungsbeiträge - Diller, Markus; Grottke, Markus; Lorenz, Johannes (Wirtschaftswissenschaftliches Studium (WiSt))

Tax Aggressiveness of Taxpayers with Heterogenous Income and Uncertainty about Taxable Income - Diller, Markus; Lorenz, Johannes (FinanzArchiv / Public Finance Analysis)

Geschichten vom ersten bis zum 38. Stock - Kostan, Anastassija (Turmgeschichten: Raumerfahrung und -aneignung im AfE-Turm)

Aging in digital circuits and age monitoring: Object-oriented modeling and evaluation - Sadeghi-Kohan, Somayeh; Kamran, Arezoo; Forooghifar, Farnaz; Navabi, Zainalabedin (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling resulting in timing variations and consequently reliability challenges in digital circuits. Age monitoring methods can be used to predict and deal with the aging problem. Selecting appropriate locations for placement of hardware aging monitors is an important issue. In this work we propose a procedure for selection of appropriate internal nodes in combinational clouds between pipeline stages or combinational parts of a sequential circuit to place hardware monitors that can effectively provide aging information of various components of a modern digital system. In order to implement the node selection procedure, we propose an object-oriented model. Object-oriented model of a circuit along with a probabilistic and logical simulation engine that we have developed can effectively be used for implementation and also fast evaluation of the proposed node selection mechanism. The proposed object-oriented C+ + models can be integrated into a SystemC RTL model making it possible to perform mixed-level simulation, and integrated evaluation of a complete system. We have applied our proposed scheme to several processors including MIPS, ARM, ALPHA and MiniRISC and have looked at its effectiveness for these processors.

Online self adjusting progressive age monitoring of timing variations - Sadeghi-Kohan, Somayeh; Kamal, Mehdi; McNeil, John; Prinetto, Paolo; Navabi, Zain (2015 10th International Conference on Design & Technology of Integrated Systems in Nanoscale Era (DTIS))
Transistor and interconnect wearout is accelerated with transistor scaling that results in timing variations. Progressive age measurement of a circuit can help a better prevention mechanism for reducing more aging. This requires age monitors that collect progressive age information of the circuit. This paper focuses on monitor structures for implementation of progressive age detection. The monitors are self-adjusting that they adjust themselves to detect progressive changes in the timing of a circuit. Furthermore, the monitors are designed for low hardware overhead, and certainty in reported timing changes.

Automating RDF Dataset Transformation and Enrichment - Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (12th Extended Semantic Web Conference, Portorož, Slovenia, 31st May - 4th June 2015)
With the adoption of RDF across several domains, come growing requirements pertaining to the completeness and quality of RDF datasets. Currently, this problem is most commonly addressed by manually devising means of enriching an input dataset. The few tools that aim at supporting this endeavour usually focus on supporting the manual definition of enrichment pipelines. In this paper, we present a supervised learning approach based on a refinement operator for enriching RDF datasets. We show how we can use exemplary descriptions of enriched resources to generate accurate enrichment pipelines. We evaluate our approach against eight manually defined enrichment pipelines and show that our approach can learn accurate pipelines even when provided with a small number of training examples.
Keywords: 2015 group_aksw sys:relevantFor:geoknow sys:relevantFor:infai sys:relevantFor:bis ngonga simba dice sherif group_aksw geoknow deer lehmann MOLE

Simplified RDB2RDF Mapping - Stadler, Claus; Unbehauen, Joerg; Westphal, Patrick; Sherif, Mohamed; Lehmann, Jens (Proceedings of the 8th Workshop on Linked Data on the Web (LDOW2015), Florence, Italy)
The combination of the advantages of widely used relational databases and semantic technologies has attracted significant research over the past decade. In particular, mapping languages for the conversion of databases to RDF knowledge bases have been developed and standardized in the form of R2RML. In this article, we first review those mapping languages and then devise work towards a unified formal model for them. Based on this, we present the Sparqlification Mapping Language (SML), which provides an intuitive way to declare mappings based on SQL VIEWS and SPARQL construct queries. We show that SML has the same expressivity as R2RML by enumerating the language features and show the correspondences, and we outline how one syntax can be converted into the other. A conducted user study for this paper juxtaposing SML and R2RML provides evidence that SML is a more compact syntax which is easier to understand and read and thus lowers the barrier to offer SPARQL access to relational databases.
Keywords: 2015 group_aksw group_mole mole stadler lehmann sherif simba dice sys:relevantFor:geoknow geoknow peer-reviewed MOLE westphal

An Optimization Approach for Load Balancing in Parallel Link Discovery - Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (SEMANTiCS 2015)
Many of the available RDF datasets describe millions of resources by using billions of triples. Consequently, millions of links can potentially exist among such datasets. While parallel implementations of link discovery approaches have been developed in the past, load balancing approaches for local implementations of link discovery algorithms have been paid little attention to. In this paper, we thus present a novel load balancing technique for link discovery on parallel hardware based on particle-swarm optimization. We combine this approach with the Orchid algorithm for geo-spatial linking and evaluate it on real and artificial datasets. Our evaluation suggests that while naïve approaches can be super-linear on small data sets, our deterministic particle swarm optimization outperforms both naïve and classical load balancing approaches such as greedy load balancing on large datasets.
Keywords: 2015 sys:relevantFor:geoknow geoknow ngonga sherif simba dice group_aksw sys:relevantFor:infai sys:relevantFor:bis SIMBA limes

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; Garcia-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Hoeffner, Konrad; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)
Keywords: 2015 group_aksw sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow lehmann ngonga MOLE sherif simba dice hoeffner geoknow wauer westphal

The GeoKnow Handbook - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; Buehmann, Lorenz; Garcia-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Hoeffner, Konrad; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Pietzsch, Rene; Isele, Robert; et al.
Keywords: 2015 group_aksw sys:relevantFor:infai sys:relevantFor:bis sys:relevantFor:geoknow lehmann ngonga MOLE sherif simba dice hoeffner geoknow westphal buehmann

Short-and medium-term effects of informal care provision on female caregivers’ health - Schmitz, Hendrik; Westphal, Matthias (Journal of Health Economics)

Jeder zehnte Mensch war illegal - Schubert, Michael (Die neuen Deutschen. Vom Dreißigjährigen Krieg bis heute: 400 Jahre Einwanderung nach Deutschland)

Soziale Ausgrenzung und rassistische Verfolgung der Osnabrücker Sinti im Nationalsozialismus - Schubert, Michael; Cooper, Duncan (Topografien des Terrors. Nationalsozialismus in Osnabrück)

Threatening customers not to return – An effective strategy for online retailers? - Feider, L.; Garnefeld, I.; Böhm, Eva (44th EMAC Annual Conference, Leuven)

Stock market reactions to customer service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (2015 AMA Winter Academic Conference, San Antonio, TX)

Recognizing value creation opportunities in business markets - Böhm, Eva; Eggert, A.; Terho, H.; Ulaga, W.; Haas, A. (2015 AMA Winter Academic Conference, San Antonio, TX)

Stock market reactions to business service outsourcing in manufacturing firms - Eggert, A.; Böhm, Eva; Cramer, C. (44th EMAC Annual Conference, Leuven)

Constitutive Effects of Technological Frames in Everyday Interaction - Klowait, Nils (Sociology of Power)

Blickfinten im Basketball: Eine EEG-Studie - Koester, Dirk; Schütz, Christoph; Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. Tagungsband der 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Treffen ohne getroffen u werden: Fechter nutzen visuelle und akusti-sche Information zum Erkennen gegnerischer Angriffe - Allerdissen, M; Bläsing, Bettina; Güldenpenning, Iris; Schack, Thomas (Stressregulation und Sport. 47. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))